The Oil Palm Complex : Smallholders, Agribusiness and the State in Indonesia and Malaysia - McCarthy, John F. (John Fitzgerald), 1964-; Cramb, R. A. (Rob A.), 1951- (Book collections on Project MUSE., 2016)
The oil palm industry has transformed rural livelihoods and landscapes across wide swathes of Indonesia and Malaysia, generating wealth along with economic, social, and environmental controversy. Who benefits and who loses from oil palm development? Can oil palm development provide a basis for inclusive and sustainable rural development? Based on detailed studies of specific communities and plantations and an analysis of the regional political economy of oil palm, this book unpicks the dominant policy narratives, business strategies, models of land acquisition, and labour-processes. It presents the oil palm industry in Malaysia and Indonesia as a complex system in which land, labour and capital are closely interconnected. Understanding the oil palm complex is a prerequisite to developing better strategies to harness the oil palm boom for a more equitable and sustainable pattern of rural development.